Management of an Arabic Language Learning Program Based on Madrasah Self-Evaluation in Improving Learning Quality at Senior High School - Siti Aminah; Hakmi Wahyudi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study analyzes the management of an Arabic language learning program based on the Madrasah Self-Evaluation (Evaluasi Diri Madrasah/EDM) framework in improving learning quality at MAN 1 Mandailing Natal. Employing a descriptive qualitative approach, data were collected through observations, interviews with eight key informants (the head of the madrasah, vice principal for curriculum, Arabic language teachers, and students), and analysis of EDM reports and instructional documents. Data validity was ensured through triangulation techniques. The findings demonstrate that instructional management was implemented through four POAC stages: planning based on EDM data, organizing through a clear division of institutional responsibilities, implementation combining communicative and digital instructional methods, and supervision via academic observation and reflective evaluation. Critically, EDM integration functioned as a sustainable internal quality assurance mechanism, enabling evidence-based decision-making for teacher competency development and instructional improvement. This study concludes that the systematic integration of POAC-based learning management and Madrasah Self-Evaluation significantly enhances Arabic language learning quality and provides a replicable model for continuous educational improvement in madrasah contexts.